Strategies to Enhance Health Literacy amomg Diabetes Patients - Sinthuchai, Somchit; Dejpitaksirikul, Suda; Sawangchit, Siriporn (NU Journal of Nursing and Health Sciences, 2022)
Diabetes Mellitus is a chronic disease that cause major public health problems globally. Uncontrolled diabetes can accelerate the onset of complications of microvascular and macrovascular complications which eventually will results in the increate in morbidity and mortality. Health literacy, defined as an individual’s capacity to access, understand, and interpret health information and make appropriate health decisions, is one of the key factor which have an influence on diabetes self-management and controlling HbA1c. This article purposes strategies to enhance the health literacy among diabetes patients, by providing strategies to health care provider regarding patient’s care, which includes motivation interview, self-management education, teaching back, communication for decision making, goal setting, perceiving life experience from stories telling and tele-nursing.